Investigating the Role of Mucin as Frontline Defense of Mucosal Surfaces against Mycobacterium avium Subsp. hominissuis. (1st July 2020) - Bechler, Jessica; Bermudez, Luiz E.
Abstract : Mycobacterium avium is a human and animal pathogen that infects the host through the mucosal surfaces. Past work has demonstrated that the bacterium can interact with both the respiratory and gastrointestinal tracts. Those surfaces in the body are covered by a bilayer of a glycoprotein, mucin, which works as a physical barrier and a gel which contains antibacterial and antivirus properties. This current work shows that different strains of M . avium, in contrast to Escherichia coli, Pseudomonas aeruginosa, and Listeria monocytogenes, are not able to bind to mucins, MUC2 and MUC5b, the main mucins in the gastrointestinal and respiratory tracts, respectively. The lack of binding is due to the characteristics of the cell wall and is impaired by altering lipids, proteins, or glycolipids. M . avium, in contrast to E . coli, interacts with epithelial cells equally in the presence or absence of the mucin, suggesting that the cell wall of the pathogen can facilitate the bacterial movement through the mucin layer, towards the mucosal wall. In conclusion, the study has shown that M . avium can avoid the mucin barrier, which explains its ability to interact with the mucosal epithelium, even in absence of motion-related structures.